An iterative approach for optimal decarbonization of electricity and heat supply systems in the Great Britain. (15th June 2020) - Haghi, Ehsan; Qadrdan, Meysam; Wu, Jianzhong; Jenkins, Nick; Fowler, Michael; Raahemifar, Kaamran
Abstract: The electrification of heat supply is a widely discussed strategy for decarbonizing the heat sector in the Great Britain (GB). This impacts the electricity load duration curve and affects the optimal mix of power generation technologies. Additionally, the price of electricity and the emission from the grid determine whether the electrified heat is cost-effective and low carbon. These interdependencies necessitate adopting an integrated approach for long term planning of heat and electricity supplies to ensure cost-effective decarbonization. In this work, we have developed an iterative approach for investigating optimal mix of technologies in electricity and heat sectors considering the interactions between these sectors. This approach was applied to GB as a case study. Firstly, the capacity and operation of various technologies for electricity generation were determined to supply electricity demand (including electricity demand for heating) with a minimum annualized cost. Then, using the levelized cost of electricity calculated in the power generation mix optimization problem, the optimal heat supply mix was determined through the minimization of annualized cost. The iterative optimization of electricity and heat was continued until an equilibrium was achieved. The results were compared with a centralized optimization model that heat and electricity supply problems are solved simultaneously. Highlights: Interaction of the heat and electricity supply systems is modeled and investigated. A bilevel model is developed and solved using an interactive method. Heat and electricity supply systems are also solved using a centralized model. Comparison of two methods show the advantage of bilevel modeling of energy sectors.